Chapter 3 Sandwich Generation Women in Search for Meaningful Work and Life - Mervi Rajahonka; Kaija Villman (Emerald Publishing Limited, 2022)
This chapter discusses female managers' and entrepreneurs' views on lifelong learning. The main empirical data were drawn from interviews with 67 women participating in training and coaching programmes in South Savo, Finland, in 2017–2021. Many of the women belonged to the working sandwich generation (WSG). The particular focus was on how lifelong learning relates to these women's careers, wellbeing at work, work–life balance and search for meaningful lives. A model integrating women's earning, learning and meaning aspects of work and life was developed. The findings of the study show that considering women's fragmented work careers, lifelong learning is often crucial for them. For an individual, opportunities for lifelong learning and meaningful work assure personal development, wellbeing at work and a sustainable career. For employing organisations, offering opportunities for learning and meaningful work for their employees constitutes a competitive advantage.
10.1108/978-1-80262-501-120221004; 10.1108/978-1-80262-501-120221004; Working Women in the Sandwich Generation: Theories, Tools and Recommendations for Supporting Women's Working Lives; EBP077208358